Genealogy of Power Relations in the Authority of Qur'anic Interpretation: Acceptance of Ibn Muḥaysin Qirāʾah Shādhdhah from Michel Foucault's Perspective - Muhammad Ali Fathomi (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2026)
This dissertation examines the dynamics of the acceptance of Ibn Muhayṣin’s (d. 123 AH) qiraat within the Islamic exegetical tradition through the lens of Michel Foucault’s genealogy. The study originates from a historical anomaly revealing a “Canonization Rupture” post-324 AH, where the initially authoritative figure of Ibn Muhayṣin was transformed into a marginal entity categorized as shadhdhah. Employing an archaeological-genealogical method across five authoritative tafsir works—al-Ṭabari, Ibn 'Aṭiyyah, al-Qurṭubi, Abu Hayyan, and al-Alu>si>—this research deconstructs the power mechanisms and regimes of truth that defined the boundaries of Quranic orthodoxy. The research identifies a phenomenon termed “Zoned Functional Acceptance,” which uncovers a persistent normative-empirical gap. From a normative dimension, Ibn Muhayṣin’s readings underwent repressive exclusion from the ritual space (mihrab) for the sake of canonical stability through the disciplinary technologies of Rasm and linguistic standardization. Conversely, on an empirical level, these variants received productive inclusion as intellectual instruments and linguistic laboratories within the discursive space of exegesis (maktabah). This dynamic is mapped across three epistemic phases: the phase of authority (al-Ṭabari), the consolidation phase (Ibn 'Aṭiyyah, al-Qurṭubi and Abu Hayyan), and the disciplinary-normalization phase (al-Alu>si). Findings demonstrate that qiraat authority is not merely a technical-transmissive issue but a fluid construction of power-knowledge relations. Exegetes utilized their intellectual agency to negotiate canonical dominance through linguistic, theological, and rhetorical arguments.